Experiences of teacher stress and the impact on behaviours, health and well-being: a narrative inquiry - Wiles, Ellen (2018)
The link between stress and the teaching profession is well-established in empirical research (Hamama, Ronen, Shachar and Rosenbaum, 2013, pp731-732; Carton and Fruchart, 2014, p246; Stoeber and Rennert, 2008, p2; Shyman, 2011, p352; Travers, 2001, p130). In fact, stress is now spoken of as a given; as an ‘inescapable aspect of teaching’ (Smith and Bourke, 1992, p31) with detrimental effects on teachers’ careers and health (Klassen, 2010, p342). Regardless of any previous theories, research and interventions, teacher stress is an issue now and linked to the high levels of staff absence and the record numbers of those leaving or planning to leave the profession (Espinoza, 2015; Precey, 2015; Lightfoot, 2016).